An efficient intrusion detection and prevention framework for ad hoc networks. (10th October 2016) - Amara Korba, Abdelaziz; Nafaa, Mehdi; Ghanemi, Salim
Abstract : Purpose: Wireless multi-hop ad hoc networks are becoming very attractive and widely deployed in many kinds of communication and networking applications. However, distributed and collaborative routing in such networks makes them vulnerable to various security attacks. This paper aims to design and implement a new efficient intrusion detection and prevention framework, called EIDPF, a host-based framework suitable for mobile ad hoc network's characteristics such as high node's mobility, resource-constraints and rapid topology change. EIDPF aims to protect an AODV-based network against routing attacks that could target such network. Design/methodology/approach: This detection and prevention framework is composed of three complementary modules: a specification-based intrusion detection system to detect attacks violating the protocol specification, a load balancer to prevent fast-forwarding attacks such as wormhole and rushing and adaptive response mechanism to isolate malicious node from the network. Findings: A key advantage of the proposed framework is its capacity to efficiently avoid fast-forwarding attacks and its real-time detection of both known and unknown attacks violating specification. The simulation results show that EIDPF exhibits a high detection rate, low false positive rate and no extra communication overhead compared to other protection mechanisms. Originality/value: It is a new intrusion detection and prevention framework to protect ad hoc network against routing attacks. A key strength of the proposed framework is its ability to guarantee a real-time detection of known and unknown attacks that violate the protocol specification, and avoiding wormhole and rushing attacks by providing a load balancing route discovery.